2017
DOI: 10.1111/jace.14807
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of optical properties: Eu with Al codoping in aluminum silicate glasses and glass‐ceramics

Abstract: Eu-doped transparent oxyfluoride aluminosilicate glass was prepared by controlling with Al codoping of melt-quenched glass fabricated under air atmosphere. In the presence of Al input, the photoluminescence emission spectra under 393 nm excitation shows a blue shift by adjusting the ratio of Eu 3+ and Eu 2+ . After heat treatment of glass, the ratio of Eu 3+ and Eu 2+ of luminescence emission were changed by controlling treatment temperature. The PL intensity of Eu 3+ and Eu 2+ ions in the glass-ceramics (GC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…7 F 2 , respectively. [30] These spectroscopic differences between Eu 2 + and Eu 3 + species are significantly important features to determine the europium's oxidation states in the specific reaction with europium complexes. Indeed, Zhou's group have recently investigated and determined the changes of oxidation states for europium species doped on oxyfluoride aluminosilicate glass using the ratio of Eu 3 + and Eu 2 + of PL emission intensity.…”
Section: Entrymentioning
confidence: 99%
See 2 more Smart Citations
“…7 F 2 , respectively. [30] These spectroscopic differences between Eu 2 + and Eu 3 + species are significantly important features to determine the europium's oxidation states in the specific reaction with europium complexes. Indeed, Zhou's group have recently investigated and determined the changes of oxidation states for europium species doped on oxyfluoride aluminosilicate glass using the ratio of Eu 3 + and Eu 2 + of PL emission intensity.…”
Section: Entrymentioning
confidence: 99%
“…While the Eu 2 + from EuBr 2 showed dominant absorption band in aqueous media from l abs = 250-350 nm and weak tailed absorption traces 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 within 400 nm which is associated with transitions from the ground state (electron configuration = 4f 7 ) to the lowest excited state (4f 7 5d), [29] the Eu 3 + from both EuBr 3 and Eu(NO 3 ) 3 showed nearly no peaks in the UV-Vis spectra (Figure 1(a)). [30] These spectroscopic differences between Eu 2 + and Eu 3 + species are significantly important features to determine the europium's oxidation states in the specific reaction with europium complexes. Even though all Eu cation species showed intense emission spectra around l em = 455 nm excited at 395 nm, only Eu 3 + species from both EuBr 3 and Eu(NO 3 ) 3 showed two specifically strong emission peaks at l em = 592 nm and 616 nm, which are involved in the electronic transitions of 5 D 2 !…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…43 Zhang et al 44 reported an Eu 2+ -doped silicate SLSAKP GPP, which had a tunable emission band. Gao et al 45 used Al powder to reduce Eu 3+ to Eu 2+ in a SiO 2 -Al 2 O 3 -Na 2 CO 3 -YF 3 -NaF glass matrix. They found that the ratio of Eu 3+ to Eu 2+ could be controlled by using various amounts of Al.…”
Section: Glass Phosphor Plate (Gpp)mentioning
confidence: 99%
“…The commercial Nd 3+ ‐doped phosphate laser glasses such as N31 (SIOM China), LGH‐8 (Hoya Japan) and LG‐770 (Schott America) have been successfully applied in high peak power laser system . Yet, different from the d‐d and p‐p transition of transition and main group metal ions with tunable emission, the luminescence of RE ions originated from f ‐ f transition is relatively insensitive to the surrounding environment . Thus, it is hard to obtain broad NIR emission band from Nd 3+ ‐doped laser glass.…”
Section: Introductionmentioning
confidence: 99%